Auto-measure emphysematous parameters and pathophysiological gene expression profiles in experimental mouse models of acute and chronic obstructive pulmonary diseases - Ryunosuke Nakashima; Shunsuke Kamei; Hirofumi Nohara; Haruka Fujikawa; Kasumi Maruta; Taisei Kawakami; Yuka Eto; Noriki Takahashi; Mary Ann Suico; Toru Takeo; Naomi Nakagata; Hirofumi Kai; et al. (Elsevier, 2019)
Pulmonary emphysema, inflammation and senescence-like phenotype are pathophysiological characteristics of chronic obstructive pulmonary disease (COPD). Recently, a murine model of COPD has been established by inducing airway-specific overexpression of epithelial Na+ channel β subunit (βENaC-Tg mice). However, little is known about the histological and biochemical differences between βENaC-Tg mice and an existing acute emphysematous mouse model (elastase-induced model). Here, we first utilized whole lung image-based quantification method for histological analysis to determine auto-measure parameters, including alveolar area, alveolar perimeter, (major axis + minor axis)/2 and Feret diameter. Even though the extent of emphysema was similar in both models, the coefficient of variation (CV) of all histological parameters was smaller in βENaC-Tg mice, indicating that βENaC-Tg mice show homogeneous emphysema as compared with elastase-induced acute model. Expression analysis of lung tissue RNAs further revealed that elastase-induced model exhibits transient changes of inflammation markers (Kc, Il-6, Lcn2) and senescence-related markers (Sirt1, p21) at emphysema-initiation stage (1 day), which does not last until emphysema-manifestation stage (3 weeks); while the up-regulation is stable at emphysema-manifestation stage in βENaC-Tg mice (14-week old). Thus, these studies demonstrate that βENaC-Tg mice exhibit diffuse-type emphysema with stable expression of inflammatory and senescence-like markers. Keywords: Chronic pulmonary obstructive disease (COPD), Epithelial Na+ channel (ENaC), Emphysema, Auto-measure parameters, Senescence